THE IMPACT OF ARTIFICIAL INTELLIGENCE ON ENGLISH LANGUAGE LEARNING AND ASSESSMENT - Jovliyeva Nafosat Bahodir qizi, (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Annotation: This article explores the influence of Artificial Intelligence (AI) on English language learning and assessment in modern education. It analyzes how AI-powered technologies such as chatbots, intelligent tutoring systems, automated essay scoring, and speech recognition tools are transforming the way students learn, practice, and are evaluated in English. The study emphasizes that AI enables personalized learning experiences, provides instant feedback, and supports teachers in designing adaptive instructional methods. The article concludes that integrating AI into English language education enhances learner engagement, accuracy, and efficiency in both teaching and assessment processes.